The Use of Affiliate Marketing in Improving Pegipegi Sales - Natarina, R. A. Emilia; Anugrah Bangun, Cendera Rizky (Universitas Semarang, 2019)
The changes in people's purchasing patterns from offline to online cause companies to change the type of their business which also affects the changing of marketing strategy. One of the marketing strategies used by the OTA (Online Travel Agent) industry is affiliate marketing. This study was conducted to find out how Pegipegi affiliate marketers used the digital marketing to help market OTA products in the digital media they use to help provide sales. The method used in this study is qualitative with the case study of Pegipegi affiliate marketers. The data collection was conducted by interviewing. The results of this study indicate that the basic understanding of how to market Pegipegi products through blogs, how to market blog through Google Ads and Facebook Ads, as well as the understanding on the functions of each affiliate marketing tools play an important role in the success of a marketer of Pegipegi affiliate.